Cross-Layer Perceptual ARQ for Video Communications over 802.11e Wireless Networks. (19th August 2007) - Bucciol, P.; Masala, E.; Filippi, E.; De Martin, J. C.
Abstract : This work presents an application-level perceptual ARQ algorithm for video streaming over 802.11e wireless networks. A simple and effective formula is proposed to combine the perceptual and temporal importance of each packet into a single priority value, which is then used to drive the packet-selection process at each retransmission opportunity. Compared to the standard 802.11 MAC-layer ARQ scheme, the proposed technique delivers higher perceptual quality because it can retransmit only the most perceptually important packets reducing retransmission bandwidth waste. Video streaming of H.264 test sequences has been simulated with ns in a realistic 802.11e home scenario, in which the various kinds of traffic flows have been assigned to different 802.11e access categories according to the Wi-Fi alliance WMM specification. Extensive simulations show that the proposed method consistently outperforms the standard link-layer 802.11 retransmission scheme, delivering PSNR gains up to 12 dB while achieving low transmission delay and limited impact on concurrent traffic. Moreover, comparisons with a MAC-level ARQ scheme which adapts the retry limit to the type of frame contained in packets and with an application-level deadline-based priority retransmission scheme show that the PSNR gain offered by the proposed algorithm is significant, up to 5 dB. Additional results obtained in a scenario in which the transmission relies on an intermediate node (i.e., the access point) further confirms the consistency of the perceptual ARQ performance. Finally, results obtained by varying network conditions such as congestion and channel noise levels show the consistency of the improvements achieved by the proposed algorithm.